2011
DOI: 10.1007/s00024-011-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Slow Dynamics of Earth Materials: An Experimental Overview

Abstract: In 1996 JOHNSON et al. were the first to identify peculiar rate effects in resonant bar experiments on various earth materials. The effects were evident on time scales of minutes to hours. They were also seen in both sedimentary and crystalline rocks, and have since been seen in geomaterials like concrete. Although these effects resemble some aspects of creep and creep recovery, they can be induced by a sinusoidal acoustic drive at strains three orders of magnitude below typical creep experiments. These strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 32 publications
9
80
1
Order By: Relevance
“…Relaxation of the seismic velocity after perturbing rocks has been observed in laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & Sens-Schönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014), and is thus an observable property under the right conditions. These observations usually show a recovery similar to the relaxation shown in Fig.…”
Section: R E L a X At I O N A S A D I A G N O S T I C O F C H A N G Ementioning
confidence: 88%
See 2 more Smart Citations
“…Relaxation of the seismic velocity after perturbing rocks has been observed in laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & Sens-Schönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014), and is thus an observable property under the right conditions. These observations usually show a recovery similar to the relaxation shown in Fig.…”
Section: R E L a X At I O N A S A D I A G N O S T I C O F C H A N G Ementioning
confidence: 88%
“…Laboratory studies (Ten Cate & Shankland 1996;Zaitsev et al 2003;Vakhnenko et al 2004;Ten Cate 2011) and seismological field observations (Poupinet et al 1984;Schaff & Beroza 2004;Wegler & SensSchönfelder 2007;Brenguier et al 2008;Wu et al 2009;Nakata & Snieder 2011;Hobiger et al 2012;Nakata & Snieder 2012;Wu & Peng 2012;Brenguier et al 2014;Obermann et al 2014;Richter et al 2014;Gassenmeier et al 2016) show that the seismic velocity of rocks is often reduced during shaking, and recovers afterwards. Gassenmeier et al (2016) demonstrated that, at least in some cases, these changes are caused by the shaking of the subsurface that damages the material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our hypothesis is therefore that not only the ground shaking of large earthquakes induces transient variations in seismic velocity, but every small excitation continuously leads to such transient changes and a recovery afterward. In laboratory experiments, it was shown that the recovery of the elastic moduli follows a linear relation with a logarithmic timescale (Tremblay et al 2010;TenCate 2011 Wu et al (2009) observed a logarithmic recovery of a velocity decrease induced by a strong earthquake. These studies always investigate the effect of a single excitation and do not consider the superposition of different relaxation curves.…”
Section: Transient Velocity Variationsmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.116.115501 Nonlinear mesoscopic elastic materials [1] exhibit unique and interesting properties related to nonlinear and nonequilibrium dynamics that are relevant to various natural and industrial processes ranging in scales and applications, e.g., the onset of earthquakes and avalanches in geophysics [2][3][4], the aging of infrastructures in civil engineering [5,6], the failure of mechanical parts in industrial settings [7][8][9], bone fragility in the medical field [10][11][12], or the design of novel materials, including nonlinear metamaterials, for shock absorption, acoustic focusing, and energy-harversting systems [13]. These properties include the dependence of wave speed and damping parameters on strain amplitude [5,14,15], slow relaxation [16,17], and hysteresis with end-point memory [18][19][20]. Consolidated (see the work referenced previously) and unconsolidated granular media [21][22][23][24] are of particular interest for laboratory-scale experiments because they can provide reference measurements to study or engineer these properties.…”
mentioning
confidence: 99%